Nutritional supplements, leptin, insulin and progesterone in female Australian Cashmere goats - Shikh Maidin, Mashitah; Blackberry, Margaret A.; Miltona, J. T. B.; Hawken, Penelope A. R.; Martin, Graeme B. (Elsevier, 2013)
In small ruminants, reproductive wastage due to early embryo mortality is a major industry issue because it reduces reproductive efficiency and limits productivity. In sheep, early embryo mortality appears to be caused by reductions in progesterone concentrations when animals are over-fed, but this concept has not been studied in goats. Therefore we tested whether a supplement of lupin grain affects circulating progesterone concentrations in Cashmere goats during non- breeding season. We allocated 23 females into two groups: Controls were fed to ensure maintenance of body mass (85% chaff, 15% lupins head daily); Supplemented goats were fed twice their daily requirements for maintenance. All animals were anovulatory and treated with CIDRs to supply exogenous progesterone at a relatively constant rate. Nutritional treatments lasted for 18 days, and coincided with the presence of CIDRs. Leptin and insulin concentrations were increased (p < 0.05) by supplementation, but progesterone concentrations did not significant differ between groups at any time during the experiment. We conclude that a dietary supplement that elicits major changes in energy homeostasis does not reduce progesterone concentrations in goats and is thus unlikely to affect embryo mortality.